Leading psychoeducational groups for children and adolescents - DeLucia-Waack, Janice L.
'Leading Psycho-educational Groups for Children and Adolescents' is an applied and pragmatic approach to leading psycho-educational groups, and combines leadership skills and how to design and lead groups